Blog: strategic tool for organizational communication - Tassigny, Mônica Mota; Brasil, Marcus Vinicius de Oliveira; Bugarim, Maria Clara; Nogueira, Fábio Luiz Benício Maia (Revista de Administração da UFSM, 2012)
http://dx.doi.org/10.5902/198346594809 This study aimed to discuss the general importance of the blogs as a tool for internal and external organizational communication, highlighting as a new mode of communication that can help the information management and build a competitive corporate image, motivating the workforce customer loyalty. It is a case study, qualitative in nature, a literature review, a documentary and a field research. The documentary research was done in a site related to GoogleDocs tool. In the field research was used content analysis. As a result, it is observed that companies are implementing organizational communication processes more participative and strategic. From this perspective, it was concluded that blogs are tools with organizational power of instant two-way communication, able to ensure an interaction of information between the organization and its stakeholders, being a strategy to strengthen the image of the organization to the clients, functioning as a collaborative tool of information management.